STEAM-Integrated Problem-Based Learning: Traditional Indonesian Music on Sound Wave Concepts - Cristina Aurelia; Prima Warta Santhalia; Wahyu Hari Kristiyanto (Jurnal Penelitian Pendidikan IPA, 2023)
Conceptual understanding is the level of a student's ability to understand a certain concept and explain it without altering the original meaning. This research aims to determine students' conceptual understanding by using STEAM-integrated Problem-Based Learning on sound wave material. "Mix methods" are used in this research, which is accompanied by an embedded experimental design. The research subject consists of 37 students in 11th grade at SMA Salatiga. Based on the results, it can be concluded that Problem-based learning (PBL) can increase students' conceptual understanding of sound wave material. This is proven by the results of the analysis on their conceptual understanding; where previously it consisted of the partial understanding category (5.41%), partial misconception category (10.81%), specific misconception category (48.65%), and no understood category (35.14%) – and after using STEAM integrated PBL – it consists of sound understood category (35.15%), partial understanding category (48.64%) and partial misconception category (16.21%). In the future, STEAM-integrated PBL can be implemented in other skills, especially the ones needed in the 21st century; such as critical thinking, creativity, communication, and collaboration.